AKTIVITAS ANTIOKSIDAN EKSTRAK HEKSANA, ETIL ASETAT DAN METANOL BIJI KELOR (Moringan oleifera Lamk.) ASAL KABUPATEN MANOKWARI - Zaikana Wa Nur Umela Tangadji; Bimo Budi Santoso; Evelina Somar (FMIPA Universitas Papua, 2025)
ABSTRACT: Antioxidant activity testing of hexane, ethyl acetate (EtOAc), and methanol (MeOH) extracts of M. oleifera seeds was carried out using the DPPH method. The extraction method employed was Soxhlet extraction, which is a type of continuous extraction using an organic solvent at a specific temperature and solvent volume. The yields of each extract were 26.76%, 9.86%, and 39.02%, respectively. The antioxidant activity of the seed extracts was determined based on their IC50 values. Vitamin C was used as a positive control, with an IC50 value of 42.78 ppm. The antioxidant activities of the hexane, EtOAc, and MeOH extracts were 406.09, 399.03, and 135.83 ppm, respectively. The highest antioxidant activity was observed in the MeOH extract, which falls into the category of moderate antioxidant activity. Keywords: Antioxidant, Moringa oleifera seeds, DPPH, hexane extract, ethyl acetate extract, methanol extract